Odpowiedzi

  • Użytkownik Zadane
2009-05-15T00:14:28+02:00
A+b
A) 1+√2+1-√2 = 2
B) 1+√5+3-2√5=4-√5
C) 2+√7+1-√7=3

a-b
A) 1+√2-(1-√2) = 1+√2-1+√2=2 √2
B) 1+√5-(3-2√5)=1+√5-3+2√5=3√5-2
C) 2+√7-(1-√7)=2+√7-1+√7=1+2√7

a*b
A) (1+√2)*(1-√2) = 1-2 = -1
B) (1+√5)*(3-2√5)=3-2√5+3√5-10=√5-7
C) (2+√7)*(1-√7)=2-2√7+√7-7=-5-√7

a:b
A) 1+√2 1+√2 1+2√2+2 3+2√2
⁻⁻⁻⁻ * ⁻⁻⁻⁻ = ⁻⁻⁻⁻⁻⁻⁻⁻ = ⁻⁻⁻⁻⁻⁻⁻ = -3-2√2
1-√2 1+√2 1-2 -1

B) 1+√5 3+2√5 3-2√5+3√5-10 -7-√5 7+√5
⁻⁻⁻⁻ * ⁻⁻⁻⁻ = ⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻ = ⁻⁻⁻⁻⁻⁻⁻ = ⁻⁻⁻⁻⁻⁻⁻
3-2√5 3+2√5 9 - 20 -11 11

C) 2+√7 1+√7 2+2√7+√7+7 9+3√7 3(3+√7) 3+√7
⁻⁻⁻⁻ * ⁻⁻⁻⁻ = ⁻⁻⁻⁻⁻⁻⁻⁻ = ⁻⁻⁻⁻⁻⁻⁻ = ⁻⁻⁻⁻⁻⁻⁻ = ⁻⁻⁻⁻⁻
1-√7 1+√7 1-7 -6 -6 -2